Direct payment subsidies and the impact on farm land prices: a cross-country comparative evaluation - Rupp, Magnus (Kansas State University, 2014)
Agriculture subsidization policies have a long history and have been criticized, reformed and heavily discussed multiple times over the last centuries. However, most countries in the world use farm subsidies as a policy instrument and spend billions every year. Especially highly developed and wealthy countries seem to have a tendency to subsidize production agriculture and the agricultural industry. The objective of this thesis is to improve understanding of the impact direct payments or subsidies may have on farm land values via farmers paying higher dollars for ground they rent and capitalization of those higher rents. Analysis is done by comparing the allocation of subsidy dollars from the Common Agricultural Policy on two wheat farms in Germany and Czech Republic, which are member countries of the European Union, to wheat farms in the United States and Australia, countries with relatively lower subsidy levels. Data for the farms include their cost structures, total revenues, and total direct payments. Comparisons of their relative land values and rental rates paid will provide evidence to test the hypothesis that direct subsidies are likely to increase land values. Based on the economic costs of production for the farms in Germany and Czech Republic, the value of land is not necessarily the residual claimant for the direct payments paid out through Europe’s Common Agricultural Policy. Possible explanations for this include restrictions on farmland use and farmland ownership structures held over in former communist countries where farms were owned by the state. These factors are likely to affect potential farmland owners’ perceptions of property rights and their willingness to pay a full market value for land.
Keywords: Subsidy; Land; Common Agriculture Policy; Production cost; Agriculture, General (0473); Economics, Agricultural (0503)